Artificial Neural Network Analyzing Wearable Device Gait Data for Identifying Patients With Stroke Unable to Return to Work - Iosa, Marco; Capodaglio, Edda; Pelà, Silvia; Persechino, Benedetta; Morone, Giovanni; Antonucci, Gabriella; Paolucci, Stefano; Panigazzi, Monica (Frontiers in Neurology, 2021)
A potential dramatic effect of long term disability due to stroke is the inability to return to work. An accurate prognosis and the identification of the parameters inflating the possibility of return to work after neurorehabilitation is crucial. Many factors may influence it, such as mobility, and in particular walking ability. In this pilot study two emerging technologies have been combined with the aim of developing a prognostic tool for identifying patients able to return to work: a wearable inertial measurement unit for gait analysis and an artificial neural network (ANN). Compared with more conventional statistics, ANN showed a higher accuracy in identifying patients with respect to healthy subjects (90.9% vs 75.8%), and also in identifying the subjects unable to return to work (93.9% vs 81.8%). In this last analysis, the duration of double support phase resulted the most important input of ANN. The potentiality of ANN, developed also in other fields such as marketing on social networks, could allow a powerful support for clinicians that today should manage a large amount of instrumentally recorder parameters in patients with stroke.